Current management of metastatic castration-sensitive prostate cancer. (2021) - Kessel, Adam; Kohli, Manish; Swami, Umang
Highlights: Three novel hormonal therapies, abiraterone, apalutamide, and enzalutamide, have been approved in metastatic castrate sensitive prostate cancer. Docetaxel is recommended for patients with metastatic castrate sensitive prostate cancer while the benefit may be less certain in low-volume patients. Relugolix, is the first oral, gonadotropin-releasing hormone antagonist to be approved for patients with advanced prostate cancer. In future, somatic or germline alterations will potentially guide the management of metastatic castration sensitive prostate cancer. Abstract: Prostate cancer affects one in nine men and once metastatic is incurable. The treatment for metastatic castration-sensitive prostate cancer (mCSPC) has evolved rapidly over the last decade with the addition of upfront intensification with novel hormonal therapies (abiraterone, enzalutamide, apalutamide) or docetaxel in addition to androgen deprivation therapy. In this review, we discuss the phase III studies that lead to the approval of these upfront intensification therapies. We also review the recent approval of relugolix, the first oral, gonadotropin-releasing hormone antagonist for patients with advanced prostate cancer. A comparison of various agents is made and variables that can help in treatment selection are reviewed. We also summarize our current understanding of the role of germline and somatic alterations in the mCSPC setting. Finally, we review the ongoing clinical trials which can change the current treatment paradigm.